Analysis of Patient Safety Incident reporting system as an indicator of quality nursing in critical care units in KwaZulu-Natal, South Africa - Thusile M. Gqaleni; Busisiwe R. Bhengu (AOSIS, 2020)
Background: Patient Safety Incidents occur frequently in critical care units, contribute to patient harm, compromise quality of patient care and increase healthcare costs. It is essential that Patient Safety Incidents in critical care units are continually measured to plan for quality improvement interventions. Aim: To analyse Patient Safety Incident reporting system, including the evidence of types, frequencies, and patient outcomes of reported incidents in critical care units. Setting: The study was conducted in the critical care units of ten hospitals of eThekwini district, in KwaZulu-Natal, South Africa. Methods: A quantitative approach using a descriptive cross sectional survey was adopted to collect data from the registered nurses working in critical care units of randomly selected hospitals. Self-administered questionnaires were distributed to 270 registered nurses of which 224 (83%) returned completed questionnaires. A descriptive statistical analysis was initially conducted, then the Pearson Chi-square test was performed between the participating hospitals. Findings: One thousand and seventeen (n = 1017) incidents in ten hospitals were self-reported. Of these incidents, 18% (n = 70) were insignificant, 35% (n = 90) minor, 25% (n = 75) moderate, 12% (n = 32) major and 10% (n = 26) catastrophic. Patient Safety Incidents were classified into six categories: (a) Hospital-related incidents (42% [n = 416]); (b) Patient care-related incidents (30% [n = 310]); (c) (Death 12% [n = 124]); (d) Medication-related incidents, (7% [n = 75]); (e) Blood product-related incidents (5% [n = 51]) and (f) Procedure-related incidents (4% [n = 41]). Conclusion: This study's findings indicating 1017 Patient Safety Incidents of predominantly serious nature, (47% considering moderate, major and catastrophic) are a cause for concern.